Anxiety and depression among Tunisian women victims of domestic violence - R. Jbir; L. Aribi; W. Abid; I. Jbir; F. Charfeddine; S. Ellouze; J. Aloulou (European Psychiatry, 2022)
Introduction Violence against women is now widely recognized as an important public health problem with substantial consequences on mental health, that is why health professionals should be identifying, preventing, and responding to violence against women more effectively.